Productivity and economic feasibility of rice (Oryza sativa)-based cropping systems in north-western India - DHIMAN, S D; NANDAL, D P; OM, HARI; MEHLA, D S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1992-93 through 1995-96 with 5 rice- based cropping sequences, viz green manuring of dhaincha (Sesbania acuieata Pair) -rice (Oryza sativa L.) - wheat (Triticum aestivum L. emend. Fiori and Paol), rice - wheat, rice - potato (Solanum tuherosome L.) - sunflower (Helicnthus annuus L.), rice-toria (Brassica COmpestris var toria Duth. & Full) - sunflower and rice (scented)-sunflower at Kaul for evaluating their production potential and economic return. Total productivity, average production efficiency and land-use efficiency were highest in rice - potato - sunflower sequence, but significantly higher net returns over variable costs (Rs. 29.91 tonnes/ha) and benefit over the traditional rice - wheat sequence (40.29% higher) were recorded with scented rice - sunflower. Slight buildup in organic matter content of the soil was noticed with green manure - rice - wheat (0.38 - 0.47%) and rice - potato - sunflower (0.38 - 0.43%).